Between Evasion and Activism: A Qualitative Inquiry into the Political Behavior of German and Swedish Long-Term Unemployed - Hobbins, Jennifer; Lahusen, Christian (Partecipazione e conflitto, 2015)
This comparative article aims to understand the patterns underlying the political behavior of young German and Swedish long-term unemployed individuals. Based on almost 40 qualitative interviews, the analysis follows a grounded theory approach and shows that “unemployment” is not an objective reality that imposes uniform living conditions. Social and political activities diverge considerably, even though our respondents experience similar pressures and sanctions by public opinion, political parties, public administrations, relatives and/or acquaintances. The consequences of unemployment depend on individual mind-sets, support networks and coping strategies. This study identifies informal networks of social relations as one main factor influencing unemployed young peoples’ political behavior. Three types of political involvement are shaped by the routines and norms reproduced within their web of social relations in everyday life: evasion, civic minimalism and reluctant activism. The similarities between the German and the Swedish respondents overshadowed the national differences